Comparative Analysis Before and After Spin-Off on Financial Performance - Lea Putri, Helma; Kadir (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
Introduction/Main Purpose: This research aims to examine the influence before and after the spin-off on the financial performance of PT Pelindo Terminal Petikemas (TPK) Banjarmasin. Background of the problem: The reason a company implements a spin-off strategy is to prioritize activities that are appropriate to its field of operation, so that the company can concentrate more on appropriate business segments and is expected to improve the company's financial performance. In Indonesia, several companies are carrying out spin-offs as part of their strategy to improve long-term performance, one of the companies that is carrying out spin-offs is PT Pelindo Terminal Petikemas. PT Pelindo Terminal Petikemas-TPK Banjarmasin before 2022 will still be merged with PT Pelindo III Regional Kalimantan. After undergoing a spin-off process on February 1 2022, PT. Pelindo III Regional Kalimantan and PT. Pelindo Terminal Petikemas (TPK) Banjarmasin is no longer under one management. Research gap/Novelty: Previous research results are still inconsistent. PT Pelindo, which has just carried out a spin-off, needs to compare its financial performance before and after implementing this strategy. Further analysis of financial statements and financial ratios can provide an overview of the strategic impact of this spin-off on the company's financial health. Research methods: This research is descriptive qualitative research using financial report data and financial ratios as well as interviews with related parties. Findings/Results: Based on the analysis of the Current Ratio, Cash Ratio, and Debt to Equity Ratio, PT Pelindo's performance before the spin off was better. However, the results of the net profit margin analysis show an increase in operational efficiency and company cost management. Conclusions and implications: After carrying out the spin off, PT Pelindo must improve the company's financial performance so that it can reach industry standards. Keywords— Spin-off, Financial Statement Analysis, Financial Ratios, Financial Performance;